A multivalent aptamer-based electrochemical biosensor for biomarker detection in urinary tract infection. (1st September 2021) - Naseri, Maryam; Halder, Arnab; Mohammadniaei, Mohsen; Prado, Marta; Ashley, Jon; Sun, Yi
Abstract: Lactoferrin is a multifunctional protein of the transferrin family and is known as a biomarker for various clinical diseases including urinary tract infection (UTI). However, wide concentration range of lactoferrin in urine samples due to the high interpatient variations, requires a more practical biosensor. In this article, we used a novel multivalent aptamer immobilized on the surface of screen-printed gold electrode (aptamer/SPGE) to develop the first electrochemical aptasensor for label-free detection of lactoferrin with wide dynamic detection range and high sensitivity. The performance of the fabricated biosensor was tested using electrochemical impedance spectroscopy and differential pulse voltammetry. The multivalent aptamer as the bioreceptor with high affinity and good specificity against human lactoferrin, acts to enhance the electrochemical signals and widen the working window. The aptamer/SPGE demonstrates superior sensing performances for lactoferrin in buffer solution, with a wide linear range of 10 to 1300 ng/mL with LOD of 0.9 ng/mL, as well as high selectivity, and excellent reproducibility. Besides, the constructed aptasensor was successfully applied to quantify lactoferrin concentrations in spiked urine solutions. Owing to excellent sensitivity, ease of miniaturization, simple sensing procedure, low-cost, and fast response, the proposed electrochemical aptasensor indicates a great potential towards the development of lactoferrin analysis systems, which would be helpful in the early diagnosis of UTI. Graphical abstract: Image, graphical abstract